Revision and phylogenetic analysis of Chilicola sensu stricto (Hymenoptera: Colletidae) with the description of a new species - Gibbs, Jason; Packer, Laurence (Zootaxa, 2006)
The bee subgenus Chilicola sensu stricto Spinola (Colletidae: Xeromelissinae) is revised. The male and female of Chilicola (Chilicola) luzmarieae Gibbs and Packer, new species are described based upon material from Chile. New descriptions are also provided for the five additional species of this subgenus. A key to species is provided. A phylogenetic analysis of the subgenus shows that Chilicola s. str. and Chilicola (Chilioediscelis) are each monophyletic and sister groups to one another.